Advancements in waste-to-energy (WtE) combustion technologies: A review of current trends and future developments - Agapi Vasileiadou (Discover Applied Sciences)
Abstract A global scientific interest is observed for alternative utilization of biomass wastes in the context of circular economy. Transforming waste into biofuels is a sustainable solution for dealing with global environmental issues. This article reviews recent trends and the development of biomass waste combustion technologies for energy recovery. Not only the latest scientific progress on combustion processes but also several innovative advanced technologies, such as carbon capture and storage (BECCS) technologies, oxy-fuel combustion, and chemical looping combustion (CLC) are analyzed. More specifically, combustion technologies such as fixed bed combustion, bubbling fluidized bed combustion (BFBC), circulating fluidized bed combustion (CFBC), pulverized fuel combustion (PC), oxy-biomass combustion in pulverization systems (Oxy-PC), oxy-biomass combustion in Bubbling fluidized bed combustors (Oxy-BFB), oxy-biomass combustion in circulating fluidized bed systems (Oxy-CFB), and biomass chemical looping combustion (CLC) are analyzed. Advantages and limitations of each advanced combustion method are also discussed. In addition, recent applications of artificial intelligence (AI) and machine learning (ML) for optimizing bioenergy processes and mitigating greenhouse gas (GHGs) emissions are presented. The combination of these advanced combustion technologies (CCS/CLC) with intelligence tools (AI/ML) can lead to enhanced combustion efficiency, reduced secondary wastes, better waste management, and reduced emissions. This comprehensive analysis could assist scientists and decision-makers in choosing the appropriate sustainable advanced waste-to-energy (WtE) technology. More studies should be performed in advanced AI-based smart bioenergy production to optimize the best solution in alternative feedstocks, operating parameters, green nanomaterials, and zero emissions for enhanced plant performance and reduced environmental issues.